Utilizing Wood Waste as an Alternative Material for Making Prayer Beads - Sholihin, Muhammad Rijalus; Indrianasari, Neny Tri; Sochib, Sochib (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The Tasbih Craftsmen Group which is located in Tanjungsari Village, Umbulsari District, Jember Regency is also still in most other businesses, namely the need for guidance in order to be able to select and sort out good and correct alternative raw materials in order to produce good and according to expectations. In terms of raw materials, especially regarding the selection of raw materials in order to produce goods, it should be really available and have added value, not a few business actors have minimal knowledge and mastery of it, which is based on several factors such as lack of experience and utilization in providing raw materials, therefore the selection of alternative raw materials in producing goods needs to be considered. Therefore, through this community service program, it can help companies in selecting and providing raw materials for making prayer beads. The result of this service is a raw material that is easy to use, coffee wood, which is abundant wood waste for the Tasbih Craftsmen Group, which is located in Tanjungsari village, Umbulsari District, Jember Regency, including producing scientific articles that can be published in journals or the like.